Area of Interest of Indonesian Researches in Medical and Health Professions Education: Future Direction - Mora Claramita; Gandes Retno Rahayu; Rahmi Surayya; Abu Bakar; Murti Mandawati; Michael Andreas Leman; Ova Emilia (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2017)
Background: Medical education research has been flourished in the past two decades in Indonesia. It is highly important to study results of medical education researches in Indonesia to provide future direction for medical education. Six published literature in medical education from Asian context was used as the basis of this study.Method: We used the narrative review in which quantitative data were interpreted qualitatively. All national and international publication and the unpublished research in medical education from Indonesia between 2000 - 2013 were collected with multiple methods based on 8 criteria of inclusion/ exclusion. We also grouped the articles into quantitative and qualitative groups based on each method in each study.Results: Total articles interpreted was 151 and grouped into 17 areas of interest and level of evidences from ‘very rarely’ to ‘very frequently’ studied. Studies in the area of understanding problem–based learning (PBL) are still dominating the area of interest including the student-assessment within PBL program. Other areas are still rarely done, especially research in health professions education other than medical doctors.Conclusion: Research in medical education in Indonesia should be more stimulated; in terms of numbers and quality, more importantly to strive for future agent of culture, socio-economic and political changes based on the actual community problems in the universal coverage era toward solid interprofessional team work to accomplish patient safety.